PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA KARYAWAN DEPARTEMEN PRODUKSI PT. PRAKARSA ALAM SEGAR - Pupung Purnamasari; Agung Surya Dwianto; Renardi Dewanto (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
In the midst of competitive conditions in the industrial world which is full of uncertainty, competitors that continue to emerge, and the intensity of change is so high, it forces the company to always continue to make improvements and innovations, in order to remain relevant to changes that are constantly happening. One of the ways that organizations can take, in order to be able to make continuous improvements, as well as spawn breakthroughs that are liked by consumers, is to increase the competence of their employees, so that they are motivated to perform better, in order to achieve organizational goals. The purpose of this study was to determine and analyze the effect of competence and motivation on employee performance in the production department of PT. Prakarsa Alam Segar. The research method used is associative quantitative research method, where the data collection method is carried out by distributing questionnaires. The population in this study were all employees of the production department of PT. Prakarsa Alam Segar totaling 61 people. Sampling was done by saturated sampling method. Data processing using SPSS version 26 software, with descriptive analysis and hypothesis testing multiple linear regression analysis. The results showed that: (1) partially the competence variable had a positive and insignificant 6% influence on the performance of the employees of the production department of PT. Prakarsa Alam Segar; (2) partially the motivation variable has a positive and significant 53.52% influence on the performance of the employees of the production department of PT. Prakarsa Alam Segar; (3) Simultaneously there is a positive and significant effect between the competence and motivation variables of 59.3% on the performance of the employees of the PT. Prakarsa Alam Segar.